2016
DOI: 10.1136/injuryprev-2015-041740
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of technology-based interventions for unintentional injury prevention education and behaviour change

Abstract: There is much potential for computer-based programmes to be used for injury-prevention behaviour change. The reviewed studies provide evidence that computer-based communication is effective in conveying information and influencing how participants think about an injury topic and adopt safety behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 72 publications
0
41
0
2
Order By: Relevance
“…For example, virtual swimming in the air does not replicate the physical fidelity connected with moving water. A previous systematic review also showed that virtual reality applications have the ability to change behavior but have little gain in knowledge (Omaki et al, 2016). While cognitive functions are crucial for the functional autonomy, Monteiro-Junior et al (2016) showed that a single bout of virtual real-ity training does not have any effect on cognitive function in older adults.…”
Section: Learning and Skill Acquisitionmentioning
confidence: 99%
“…For example, virtual swimming in the air does not replicate the physical fidelity connected with moving water. A previous systematic review also showed that virtual reality applications have the ability to change behavior but have little gain in knowledge (Omaki et al, 2016). While cognitive functions are crucial for the functional autonomy, Monteiro-Junior et al (2016) showed that a single bout of virtual real-ity training does not have any effect on cognitive function in older adults.…”
Section: Learning and Skill Acquisitionmentioning
confidence: 99%
“…Recent studies suggest that technology-based interventions can reinforce the effectiveness of injury prevention, and improve parents’ knowledge of child safety [16-18]. A systematic review of technology-based interventions for unintentional injury prevention highlighted 10 parenting interventions for child safety; all interventions were demonstrated to improve parents’ injury prevention behaviors [19]. For instance, a study by Van Beelen et al revealed that a Web-based intervention increased parents’ behavior toward child safety more than a standard leaflet related to scheduled childcare counseling [20].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study by Van Beelen et al revealed that a Web-based intervention increased parents’ behavior toward child safety more than a standard leaflet related to scheduled childcare counseling [20]. Only two interventions evaluated changes in safety knowledge, and both showed positive changes [19]. A study by Gielen et al reported that an online intervention had a positive effect on enhancing safety knowledge [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tailored injury prevention programmes have been shown to be effective at increasing the adoption of parental safety practices (A C Gielen et al ; Andrea Carlson Gielen et al ; Omaki et al ). For example, Safe N' Sound (SNS) delivers tailored information to parents of children ages 0–4 about specific unintentional injury prevention practices indicated by a self‐assessment and has been shown to be efficacious in improving parental safety behaviours (Nansel et al ; Weaver et al ; Brixey et al ).…”
Section: Introductionmentioning
confidence: 99%